(untitled) (Journal of Engineering, 2013)
Expansive soils are recognized by their swelling potential upon wetting due to the existence of some clay minerals such as montmorillonite. An effective solution was found to avoid the danger of such soils by using piles. A single pile embedded in an elasto-plastic expansive soil has been analyzed by using one of the available software which is ABAQUS to investigate the effect of applied loads on pile’s top and investigate the effect of swelling soils on load carrying capacity of the pile. The result shows that as the pile is axially loaded at its top, the axial force along the pile gradually changes from (tension) to (compression) and the pile tends to move downward. The applied load needed to initiate pile’s settlement depends on pile’s embedment depth and the depth of active zone. The ultimate carrying capacity of a single pile for no swelling conditions is greater than that of with swelling conditions.